Big data for smallholder farmers: The case of MUIIS Uganda - Pedrick, Clare (Technical Centre for Agricultural and Rural Cooperation, 2018)
There is massive scope for linking farmers to valuable knowledge and agricultural services through Information and Communication Technologies (ICTs) as a pathway to driving improved productivity and market access, creating opportunities for higher incomes and better food security as a result. In Uganda, as in many sub-Saharan countries, lack of timely and accurate access to information about weather, financial services, crop management, markets and climate coping mechanisms is a serious obstacle for smallholder farmers, preventing them from achieving higher yields and selling their produce for better prices. To address these challenges, an innovative initiative is showcasing how ICTs can be used to capture satellite-based information on a wide range of agricultural indicators, packaging it into tailor-made messages for farmers in local languages.